(untitled) (Journal of Decolonising Disciplines, 2020)
This paper advocates for the value of research into rurality in southern Africa as a means of contributing to the reversal of the geopolitics of knowledge on teaching and learning in higher education, which traditionally favours the global North. A strong qualitative research method facilitating this exploration is the use of drawings in a method known as participatory learning and action, which is appropriate in resource-constrained environments such as those found in southern Africa. We first discuss literature on rurality and the use of drawings as research techniques, after which we consider the research settings (southern African higher education), with a short comparison between conditions in various countries. We conclude with a detailed presentation of an experiential session with five members on the use of drawings, providing examples of the value as well as the challenges of this participatory research method.